INTEGRASI TEKNOLOGI CLOUD COMPUTING BERBASIS JEJARING SOSIAL PADA APLIKASI TELEMEDICINE UNTUK MENUNJANG PELAYANAN KESEHATAN MASYARAKAT - Khairan, Amal; Jamil, Mohamad; Fuad, Achmad (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2014)
The idea of examination and health evaluation with the use of telecommunications network software development is increasingly rising, due to advances in the field of multimedia, imaging, computer, information and telecommunication systems one of which is telemedicine. Along with advances in computer technology and digital systems at present, the development of telemedicine is growing. Medical equipment can produce digital images directly, but it also can convert video images into digital images. Now, the use of telemedicine is very widespread until now applied in the United States, Greece, Israel, Japan, Italy, Denmark, the Netherlands, Norway, Jordan, India, and Malaysia. In Indonesia, the development of telemedicine technology is hindered due to lack of infrastructure and information technology services owned inadequate. The purpose of this study is to design architecture telemedicine based social networking that integrates with cloud computing technology to support public service healthKeyword : Telemedicine, Cloud Computing, E-Health, Internet